Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J. (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects